An insight into gill microbiome of Eastern Mediterranean wild fish by applying next generation sequencing - Itay, Peleg; Shemesh, Eli; Ofek-Lalzar, Maya; Davidovich, Nadav; Kroin, Yael; Zrihan, Shlomi; Stern, Nir; Diamant, Arik; Wosnick, Natascha; Meron, Dalit; Tchernov, Dan; Morick, Danny (Frontiers in Marine Science, 2022)
Bacterial diseases of marine fish inflict significant economic damage to fisheries and aquaculture and pose an increasing risk to public health. When addressing fish disease, an accumulating body of research suggests adding another factor to the classic epidemiological triangle of host-environment-pathogen: the microbiome. The gills, being a gateway into the fish body and bearing an important role in fish homeostasis, have been found to be a proxy of the gut microbiota as well as reflecting the microbial communities of surrounding water. In this study, 16S rRNA amplicons of bacterial DNA extracted from the gills of 89 asymptomatic specimens of three wild fish species (Pagrus caeruleostictus, Scomber colias and Saurida lessepsianus) were sequenced using Next Generation Sequencing methodology (NGS). Data analyses revealed the presence of 41 potentially pathogenic species, including several zoonotic agents. Five genera known to include widespread and potentially pathogenic species were chosen for further investigation: Photobacterium, Shewanella, Staphylococcus, Streptococcus and Vibrio. Of these, Photobacterium and Shewanella proved the most prevalent and abundant, making up 30.2% and 11.3% of the Bluespotted seabream (P. caeruleostictus) gill microbiome alone. Photobacterium damselae and Shewanella baltica were most common at the species level. The remaining genera - Vibrio, Staphylococcus and Streptococcus – were less prevalent, and at a species level were comprised of only 1−4% potentially pathogenic representatives. Gill microbiomes exhibited host species specificity, with strong correlations between certain bacterial taxonomic groups. No definite obligatory pathogenic bacteria were found in this study, and it was suggested that pathogenic species are present as either covert pathobionts or as opportunists of the fish found to host them.